Pharmacotherapeutic Patterns and Patients’ Access to Pharmacotherapy for Some Rare Diseases in Bulgaria – A Pilot Comparative Study - Kamusheva, Maria; Dimitrova, Maria; Tachkov, Konstantin; Petrova, Guenka; Mitkova, Zornitsa (Frontiers in Pharmacology, 2021)
Provision of the latest innovative and advanced therapies for rare diseases (RDs) patients, following the international therapeutic recommendations, is crucial and necessary for both practitioners and patients. The goal is to assess the access of Bulgarian patients with the most cost-consuming RDs to medicines and to compare the pharmacotherapeutic patterns in Bulgaria and the relevant European professional associations. Pharmaco-therapeutic guidelines for treating the most cost-consuming RDs in Bulgaria were analyzed to assess their compliance with the European ones. Market entrance was evaluated through analysis of the availability of medicines in the Positive Drug List (PDL) and their date of inclusion since marketing authorization. Guidelines` compliance index was calculated and patient access was analyzed through evaluation of the National Health Insurance Fund (NHIF) standards, which provide additional criteria for treatment initiation. The analyzed guidelines follow the adopted recommendations by the relevant European professional associations. NHIF have exclusion and inclusion criteria for initiating treatment with medicines for rare diseases and for continuation. The average time-lag between centralized procedure approval and inclusion in the Bulgarian PDL for orphan medicinal products (MPs) is 6.75 years. (SD=4.96) with the longest time observed for eptacog alfa (20 years) and the shortest for rurioctocog alfa pegol, octocog alfa and simoctocog alfa (1 year). Bulgarian patients with cystic fibrosis with pulmonary manifestation had a wait time of only 1.6 years to get access to innovative, centrally authorized medicines, whereas the period for access to acromegaly treatment was 8.2 years. The main factors influencing market entrance and patient access are the time to inclusion in the PDL and the NHIF criteria.